240 A COMPARISON OF THE ISAR AND THE CLINICAL FRAILTY SCALE TO PREDICT MORTALITY AND ED RE-ATTENDANCE IN OLDER ED ATTENDERS. (18th November 2021) - Leahy, A; Corey, G; O'Neill, A; Higginbotham, O; Devlin, C; Barry, L; Cummins, N; Gabr, A; Shanahan, E; Shchetkovsky, D; Ryan, D; O'Connor, M; et al.
Abstract: Background: Frailty Screening is one method by which we can risk stratify older adults to urgent assessment in the Emergency Department. The ISAR (Identification of Seniors at Risk) and Rockwood Clinical Frailty Scale (CFS) are two frailty screening tools. We assessed the validity of these tools at predicting adverse outcomes for older adults presenting to the Emergency Department. Methods: This was a prospective cohort study. Patients over 65 were recruited, baseline demographics were obtained and a research nurse assessed them using both the CFS and ISAR. Patients were assessed by telephone interviews at one month and six months. The outcome measures assessed were mortality, ED re-attendance, hospital readmission, functional decline and institutionalisation. Results: 419 patients were recruited. 53.3% (223) were male with a median age of 76 (IQR = 10). At baseline, the median ISAR was 2 and CFS was 5. The mortality rate was 5.4% and the rate of ED re-attendance was 16.9% at one month. The relative risk of ED re-admission with an ISAR score ≥ 2 was 1.84 (1.12, 3.02) and CFS > 4 was 1.85 (1.08, 3.16). The ISAR tool ≥ 2 had a sensitivity of 74% (95% CI = 62.44, 83.99) and specificity of 41% (95% CI = 35.90, 46.61) when used as a diagnostic tool for ED re-admission at one month. The CFS > 4 had a sensitivity of 71% (95% CI = 57.79, 82.70) and specificity of 45% (95% CI = 39.33, 51.23) for ED re-attendance. Conclusion: The ISAR tool ≥ 2 was more sensitive at predicting ED reattendance at one month in comparison to the CFS. We advocate to use this tool in the ED setting to highlight those at greatest risk of adverse outcomes and those most likely to benefit from Comprehensive Geriatric Assessment.